PENGARUH LIKUIDITAS DAN SOLVABILITAS TERHADAP PROFITABILITAS PADA PERUSAHAAN TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2018-2023 - Amilia Ningsih, Vani; Sawukir (Journal of Research and Publication Innovation, 2024)
The aim of this research is to determine the the effect of liquidity and solvency on profitability in telecommunication companies listed on the Indonesia Stock Exchange for the period 2018-2023. Liquidity is proxied by Current Ratio, solvency is proxied by Debt to Asset Ratio, while profitability is proxied by Return On Asset. The method used is quantitative method using secondary data in the form of company financial statements. The population in this study were 18 companies, using purposive sampling technique, so that 7 telecommunications companies listed on the IDX were obtained that met the criteria. Data analysis using panel data regression models with the estimation used is the Random Effect Model (REM) model. The results showed that partially Current Ratio has a significant negative effect on Return On Asset. Meanwhile, Debt to Asset Ratio has a significant negative effect on Return On Asset. Simultaneously, Current Ratio and Debt to Asset Ratio have a significant effect on Return On Asset in telecommunications companies listed on the Indonesia Stock Exchange for the period 2018-2023.